The Impact Of Workload On Job Performance Among Doctors In The Public Sector - Rusli, Ahmad; Lee, Mei Yuan; Abg Ekhsan, Abang Othman; Ahmad Sofian, Shminan; Heng, Chin; Sumilan, Helmi; Abang Ahmad, Abang Izhar (Universiti Malaysia Sarawak (UNIMAS), 2017)
This research is focused on exploring the impact of workload on job performance among doctors in a public hospital. A qualitative approach was used and the method is used by the researcher is open-ended questionnaires. Purposive sampling was used in order to collect the data from informants. In this studied, four informants are doctors at the public hospital, Sarikei, Sarawak. Data analysis used by the researcher in this studied is content analysis. Based on the research findings, factors which contribute to the workload among doctors such as insufficient staff, the number of patients, inadequate equipment, inappropriate working hours and so on. In addition, the short term impact of workload on doctors’ performance can be positive and negative. But, the long term impact of workload on doctors’ performance more on negative impact such make a mistake, intention to leave organization, mental and physical health problem, decrease family relation and increasing divorce rates. This study also proposes related research implication and recommendation for further research.